PROPOSTA DE UM MODELO DE POSICIONAMENTO ESTRATÉGICO PARA IES BRASILEIRAS - Freitas, Paulo Robert C. F. de (2004)
This Thesis discusses the last ten years higher education competitive scenery. In fact, it became much more competitive and the Institutions have been developing some news management competences. In that case, it must reach a competitive advantage using a correct strategic alternatives. On the other hand, the classic competitive strategy models, like PORTER Generic Strategies , is not available to be considered in a brazilian higher education context as it has some peculiarity. So, to develope some strategy analysis, it s necessary to consider a news drivers. Academic qualifications and management innovations appears as new issues to be considered in a new model. It was developed based on a deep theoretical study and a research including eight brazilian Universities.